2016
DOI: 10.1002/ece3.2296
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly complex gradation of coral population structure in the Nansei Islands, Japan

Abstract: To establish effective locations and sizes of potential protected areas for reef ecosystems, detailed information about source and sink relationships between populations is critical, especially in archipelagic regions. Therefore, we assessed population structure and genetic diversity of Acropora tenuis, one of the dominant stony coral species in the Pacific, using 13 microsatellite markers to investigate 298 colonies from 15 locations across the Nansei Islands in southwestern Japan. Genetic diversity was not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 88 publications
6
26
0
Order By: Relevance
“…They detected strong historical migration from the Yaeyama Islands (YIs) to Okinawa Island. Zayasu et al () reported from 13 microsatellite markers of A. tenuis sampled at 15 location across the Nansei Archipelago that genetic population structure is complex as gene flow not only occurs from south to north but also from north to south in various locations. Hence, the YIs and the Amami Islands (the islands #3–7 in Table ) are potential northern and southern sources of corals, while Miyako Island (#11) and west central Okinawa Island are potential sink populations.…”
Section: Discussionmentioning
confidence: 99%
“…They detected strong historical migration from the Yaeyama Islands (YIs) to Okinawa Island. Zayasu et al () reported from 13 microsatellite markers of A. tenuis sampled at 15 location across the Nansei Archipelago that genetic population structure is complex as gene flow not only occurs from south to north but also from north to south in various locations. Hence, the YIs and the Amami Islands (the islands #3–7 in Table ) are potential northern and southern sources of corals, while Miyako Island (#11) and west central Okinawa Island are potential sink populations.…”
Section: Discussionmentioning
confidence: 99%
“…Zayasu et al. (2016), studying Acropora tenuis in southwestern Japan, hypothesized the existence of two source populations (two genetic clusters) in both farthest sites of the sampling area and a mix of both clusters in the middle of the sampling area that should be linked to migration from extreme sites to the intermediate ones. A similar pattern was observed in P. damicornis β (Gélin, Fauvelot, Mehn, Bureau, Rouzé & Magalon, 2017) in Reunion Island with both clusters mixed in one intermediate site, evoking a geographic barrier or an asynchronous spawning of the most remote populations.…”
Section: Discussionmentioning
confidence: 99%
“…). For wild locations, 15 sites that had 10 or more colonies of A. tenuis within approximately 3 ha were sampled at depths less than 10 m (Zayasu et al ). For both wild and farmed samples, a branch fragment approximately 2 cm was collected from each colony and preserved in 99% ethanol.…”
Section: Methodsmentioning
confidence: 99%